Koli women preparing breakfast for the occasion - Mumbai Archive Project Team (Jio Institute, 2024)
The women in the household grind a mixture of wheat and urad dal (split black gram lentil) to make flour. This flour is then kneaded into dough, shaped into doughnut-like rings, and deep-fried to make medu vada, a traditional breakfast dish served at Koli weddings.